Description of the larva of Brachygonia oculata (Brauer, 1878) (Odonata: Libellulidae) with notes on rearing technique - Ngiam, Robin W. J.; Chan, Juliana P.s.; Khoo, Max D.y.; Kong, Eunice Y.l.; Low, Bing Wen (Zootaxa, 2021)
The larva of the genus Brachygonia Kirby, 1889 is described and illustrated for the first time based on the larvae of Brachygonia oculata (Brauer, 1878) discovered and successfully reared in Singapore. Compared to known larvae from genera in the rather heterogeneous subfamily Brachydiplacinae, B. oculata is most similar to species from the genus Brachydiplax Brauer, 1868 after comparison is made with the larva of Brachydiplax farinosa Krüger, 1902.